Differential effects of anxiety and autism on social scene scanning in males with fragile X syndrome - Crawford, H.; Moss, J.; Oliver, C.; Riby, D.M. (Journal of Neurodevelopmental Disorders, 2017)
Background Existing literature draws links between social attention and socio-behavioural profiles in neurodevelopmental disorders. Fragile X syndrome (FXS) is associated with a known socio-behavioural phenotype of social anxiety and social communication difficulties alongside high social motivation. However, studies investigating social attention in males with FXS are scarce. Using eye tracking, this study investigates social attention and its relationship with both anxiety and autism symptomatology in males with FXS. Methods We compared dwell times to the background, body, and face regions of naturalistic social scenes in 11 males with FXS (M age = 26.29) and 11 typically developing (TD) children who were matched on gender and receptive language ability (M age = 6.28). Using informant-report measures, we then investigated the relationships between social scene scanning and anxiety, and social scene scanning and social communicative impairments. Results Males with FXS did not differ to TD children on overall dwell time to the background, body, or face regions of the naturalistic social scenes. Whilst males with FXS displayed developmentally ‘typical’ social attention, increased looking at faces was associated with both heightened anxiety and fewer social communication impairments in this group. Conclusions These results offer novel insights into the mechanisms associated with social attention in FXS and provide evidence to suggest that anxiety and autism symptomatology, which are both heightened in FXS, have differential effects on social attention.
EPrint Processing Status: Full text deposited in DRO